Electrophoretlc analysis of the evolutionary relations in Drosophila species (Díptera: Drosophilidae) of the cluster martensis: D. martensis, D. starmeri and D. uniseta - ORDÓÑEZ, MARINA; ARENAS, ANGÉLICA; BETANCOURT, LUZ ANGELA; DE POLANCO, MARÍA MAGDALENA (Revista Colombiana de Entomología, 2004)
Starch gel electrophoresis was used to elucidate genetic variation at 12 isoenzyme loci among six allopatric Colombian populations of the cluster martensis (D. mertensis, D. starmeri and D. uniseta). from Santa Marta (Magdalena Department). Camarones (Guajira Department) and from the Tatacoa desert (Huila Department). This estimation was compared to phylogenetically related (D. buzzatii) and distant (D. melanogaster) species. The enzymatic divergences were inferred from genetic distances and the results allowed the identification of six levels of taxonomic divergence: Local population (D = O, 1031). subraces (D = O, 1412), subspecíes or races (D = O, 1870). species of the same cluster (D = O, 7907). species of different clusters (D = 1,0055) and specíes from different groups (D = 1,4327). Through this preliminary study, the utility of electrophoretic data as estimators of evolutionary divergence was confirmed and a possible example of allopatric speciation is suggested.